ANALYSIS OF LOVE BY USING TRINGULAR THEORY OF LOVE BY STERNBERG IN BREAKING DAWN NOVEL BY STEPHENIE MEYER. (A PSYCHOLOGICAL STUDY) - Fazriyani S Mahmud (Universitas Muhammadiyah Gorontalo, 2018)
Love is something that everyone may have. Even love is the right of every human being in the world so that everyone has the right to love and be loved by others. Generally love is a form of emotion that contains attraction, sexual desire, and attention to someone. This shows that love has several components in it including intimacy, passion, and commitment. This research is focused on analyzing love experiences by using the triangular theory of love by Sternberg on some of the characters in the novel Breaking Dawn by Stephenie Meyer. This research used a descriptive qualitative method and used Sternberg's theory to analyze the experience of love in the breaking dawn novel. The result of this research has three components in love including intimacy, passion, and commitment.Keywords: Love, Triangular of Love, Intimacy, Passion, Commitment